1988
DOI: 10.3109/14017438809106043
|View full text |Cite
|
Sign up to set email alerts
|

Closed mitral valvotomy during pregnancy:A 20-Year Experience

Abstract: Closed mitral valvotomy for rheumatic mitral stenosis was performed on 126 pregnant women (average duration of pregnancy c. 21 weeks), 91% of whom were in NYHA functional class III or IV. Associated functional tricuspid regurgitation was present in 47 (37%) of the women, and 102 (81%) had critical mitral stenosis (digitally assessed valve area less than 1 cm2). There was no surgical mortality. Postoperatively 84% of the women were in NYHA class I. Clinical evidence of pulmonary artery hypertension and tricuspi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 21 publications
1
14
1
Order By: Relevance
“…It follows that in the setting of deteriorating maternal functional class and emergency surgery, both maternal and fetal mortality increase dramatically. It has been suggested that fetal mortality as high as 50% exists for functional class III and IV patients undergoing CPB [6,7]. In a recent review, the only two maternal deaths following surgery in a period from 1992-2002, involving 22 patients, were gravid patients who presented to the OR with endocarditis and class IV functional status, which is similar to our patient at the time of her operation [6].…”
Section: Discussionsupporting
confidence: 78%
“…It follows that in the setting of deteriorating maternal functional class and emergency surgery, both maternal and fetal mortality increase dramatically. It has been suggested that fetal mortality as high as 50% exists for functional class III and IV patients undergoing CPB [6,7]. In a recent review, the only two maternal deaths following surgery in a period from 1992-2002, involving 22 patients, were gravid patients who presented to the OR with endocarditis and class IV functional status, which is similar to our patient at the time of her operation [6].…”
Section: Discussionsupporting
confidence: 78%
“…This report, however, involved only a few patients. 11 Interestingly, our patient's hemodynamic instability completely resolved after delivery, eliminating the need for valvuloplasty. This outcome strongly supports the contention that the physiologic changes of pregnancy and preeclampsia resulted in acute hemodynamic decompensation, hence delivery could be considered as a therapeutic intervention in this circumstance.…”
Section: Discussionmentioning
confidence: 93%
“…In developing countries, there is a long history of successful surgical closed commissurotomy for pregnant women. 785 …”
Section: Mitral Stenosismentioning
confidence: 99%